Chemical composition diversity of fucoidans isolated from three tropical brown seaweeds (Phaeophyceae) species - FADILAH NOR LAILI LUTFIA; Alim Isnansetyo; Ratna Asmah Susidarti; Muhammad Nursid (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lutfia FN, Isnansetyo A, Susudarti RA, Nursid M. 2020. Chemical composition diversity of fucoidans isolated from three tropical brown seaweeds (Phaeophyceae) species. Biodiversitas 21: 3170-3177. Fucoidan is a polysaccharide with high sulfate content, found in the cell walls matrix of brown seaweed. Its bioactivities vary depending on the algae species and the chemical structure. The aims of this research were to extract, purify, and characterize fucoidan from three Indonesian brown seaweed, Sargassum sp., Turbinaria sp., and Padina sp. The extraction was carried out using acid method followed by precipitation with ethanol and CaCl2, while its purification using DEAE-cellulose ion-exchange chromatography. Characterization was performed by FTIR and 1H-NMR spectroscopic analyses. Chemical components of fucoidan determined were total carbohydrates, sulfate residue, uronic acid residue, and monosaccharide components. The results revealed that the Turbinaria sp. produced highest yield of fucoidan (4.8% dry matter), followed by Sargassum sp. (2.7% dry matter) and Padina sp. (2.6% dry matter). The carbohydrate contents of Sargassum sp., Turbinaria sp. and Padina sp. fucoidan were 64.55±0.12%, 67.42 ± 0.03% and 62.90 ± 0.04% with sulfate residues of 0.013% ± 4.71; 19.47±0.002% and 0.016%±8.81; and uronic acid residues of 25.19±0.03%; 12.69±0.03% and 12.91±0.01%, respectively. Sargassum sp., Turbinaria sp., and Padina sp. fucoidans consist of fucose and some other minor monosaccharides.